TOURISM AREA DEVELOPMENT STRATEGY TO IMPROVE COMMUNITY WELFARE - Mukaffi, Zaim; Rozi, Choirul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study aims to: 1) determine the objective conditions of the Blue bay tourism area, 2) analyze the strategy of developing Blue bay tourism in Banyuwangi Regency, 3). How is the economic potential generated in the development of the blue bay tourist area. The analytical technique used in this research is descriptive qualitative. The results of the study 1) the blue bay tourism area is an unspoiled marine tourism with the advantage of being able to enjoy marine tourism such as diving, snorkeling, etc. 2). The SWOT analysis technique shows that the IFAS position index is +0.719 and the EFAS position index is +0.641. This shows that the SWOT diagram is in Quadrant I, namely an aggressive strategy, this means that the strategy used in the development of blue bay tourism is to use strength as the basis of excellence (S) with support from opportunities (O) in its future development. 3) With the development of this tourist area, it can create community income either directly (fixed rental income) or indirectly such as homestays, providing food for tourists, stalls and others.